Trace metals biogeochemistry in soils and plants affected by mining waste rocks: consequences to ecosystem and options for restoration (Phytoremediation abd technosols) - Perlatti, Fabio (2015)
The extraction and processing of metallic minerals generate large amounts of waste which, if not disposed of properly, may be sources of contamination and acid mine drainage; by contact of sulphides with water and oxygen; causing a decrease in pH and an increase in the mobility of metals in the soil. The diagnosis of biogeochemical behaviour of wastes can provide valuable information to discard and control the adverse effects of this kind of material, as well to support the adoption of more efficient measures of control and mitigation. This study had as general objective diagnose the impacts of waste disposal in an abandoned copper mine (Cu), as well to propose alternatives to mitigate the impacts and restore the environmental quality of the site, based on the hypothesis that such wastes can contaminate the soil with trace elements contained in minerals, and generate acid mine drainage, given the presence of sulphides exposed to weather conditions, hindering the natural regeneration of the ecosystem. The Chapter 1 provides an introduction to the theme, as well as a literature review. Chapter 2 presents a general diagnosis from the area, assessing the levels of several trace elements in rock wastes, soils and native plant species. In chapter 3, a thorough study on the geochemical behaviour of wastes, with focus on the generation of acid drainage were done, plus a detailed study about Cu behaviour in soils, through a chemical sequential extraction. Chapter 4 details the content of metals in above-ground tissues from plants that naturally grow on the wastes, assess the ability of these plants to be used in phytoremediation and show data about the changes that occur in the rhizosphere. Chapter 5 provides through a comparative study by sequential extraction in the rhizosphere and bulk soils; details about the changes that occur in the rhizosphere of plants and their consequences for Cu mobility and ecotoxicity, and finally, the chapter 6 presents an experimental study with the use of technosols, as way to immobilize the excess of labile copper in soil solution. Based on the results, can be concluded that the major impact is caused by the excess of Cu which still persists in the waste rocks and, through oxidation and dissolution processes, translocate large amount of metal into soil. The acid mine drainage was discarded given the buffering action generated by dissolution of carbonates, minimizing the negative effects of the oxidation of sulphides. The sequential extraction showed that the Cu concentration in soil is associated mainly with carbonates and amorphous iron oxides. The geochemical cycle between the dissolution of carbonates and oxidation of sulphides appears to be the main control mechanism of release and adsorption of Cu in soil. Regarding the plants, was concluded that they cannot be considered as Cu hyperaccumulators, however, high levels of metal were observed in roots, indicating that the survival strategy of these plants consists in immobilize metal in roots/rhizosphere. The sequential extraction in the rhizosphere showed that the presence of plants alter various soil characteristics under its influence, and also the geochemical behaviour of Cu. The technosols showed great ability to immobilize Cu. The four technosols elaborated in this study can immobilize more than 85% of Cu in solution, with the largest portion retained in the residual fraction, where Cu is adsorbed strongly, demonstrating that technosols emerge as an excellent alternative to remediate soils contaminated by metals.